(3LGeY GdHjGf Yf JChjd Bi GdaQbGfs - (3eMeO Hf LQjQ Hf jRjO GdWHQj , GHf LQjQ, CHh LYaQ, J (B310 (3g` s
(3ChdgG (B:s
(3hChd eG ajg CKfGA JaSjQ GdBjI GdcQjeI (B" (3Ndb GdSehGJ hGdCQV hEdjg GdeUjQ (B" (3ef ShQI GdJZGHf jHOC Hbhdg (B: (3hGdCQV HGdYOd hGdCfUGa s
(3BNQgG (B:s
(3BNQ GdehLhO efg HPcQ GdBjI GdcQjeI (B" (3hEfG CYJOfG ddcGaQjf SdGSdG hCZdGdG hSYjQkG (B" (3ef ShQI GdEfSGf s
(3HgG HJQ HYO GdhQbI GdKGfjI CKfGA ShQI GdJZGHf hcPdc HYO Gds
(3bWYI efg JTJed Ydi JaSjQ BjGJ ef ShQI GdJZGHf , GdWdGb GdJMQje GdLf , GdeRed , GdeOKQ , GdbjGeI , GdEfSGf , fSNI Ydi Qb ZRGds
(3fSNI Ydi Qb ZRGds
(3ef JMHjS GdSdWGf CHj YHO Gddg GdefJUQ GdeQjfi HJGQjN (B827 (3g` s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B69 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B147s
Keywords: (3GdJaSjQ hYdhe GdbQBfs